(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Candida species are responsible for various clinical manifestations from mucocutaneous overgrowth to blood stream infections especially in immunocompromized situations. Although C. albicans is the most prevalent species, high incidence of non-albicans Candida species with antifungal resistance are emerging which is posing a serious threat to the patients care. Objective: This study aimed to isolate and identify different species of Candida from different clinical specimens. Methods: A total of 100 different clinical specimens were studied of which 35 were oral swab, 28 were high vaginal swab, 15 were urine, 14 were nail, 04 were bronchoalveolar lavage and peritoneal fluid were 04. Among 100 clinical specimens, Candida isolates were identified in 64 specimens. Isolation of Candida species was done by primary culture in SDA. Subsequent identification of species were performed by germ tube test, subculture in chromogenic agar medium and carbohydrate assimilation test with commonly used twelve sugars. Results: Out of 64 isolated Candida species, Candida albicans were 51.56% and the non-albicans Candida species were 48.44%. The most prevalent Candida species was C. albicans 33 (51.53%) followed by C. tropicalis 17 (26.56%). C. glabrata 4 (6.25%), C. parapsilosis 4 (6.25%), C. krusei 3 (4.68%) and C. guilliermondii 2 (3.2%). One of the isolated Candida species was unidentified. Conclusion: Though Candida albicans was found as the most common species, but non-albicans Candida species are appearing as emerging pathogens as well. Exposure to chemotherapy appeared to be the commonest predisposing factor for Candida infection followed by indwelling urinary catheter in situ for prolong period.